El teletrabajo como factor de riesgo asociado al síndrome de burnout en el personal administrativo de la Universidad Técnica de Cotopaxi. - Amaya Simba, Julio Andrés (2021)
This research project is of great importance since it will reflect what burnout syndrome can cause to workers who are fulfilling their working hours in the teleworking modality, since in these times of pandemic these workers are forced to adapt to this. type of work so, being exposed for long periods of time sitting in front of a computer can seriously affect your health in the short or long term. Otherwise, this research presents teleworking as a work modality that has been implemented as a strategy to stop the spread of Covid-19, but since it is suddenly and mandatory, many workers are subject to risks such as burnout syndrome, for what our contribution will be to measure the professional wear on the feelings and attitudes of the professional in his work environment. This research will benefit the administrative staff of the Technical University of Cotopaxi since it will be possible to feel this reality in a close way, and then propose alternative solutions that allow responding to the needs of the participants; because based on this study, they will have a better understanding of this problem and all the effects it can trigger in the workplace as well as in the social sphere.